UV light induced DNA damages and the radiation protection effects of Lingzi mushrom extract - Vo Thi , Thuong Lan; Dinh , Ba Tuan; Ta , Bich Thuan; Tran , Bang Diep; Tran , Minh Quynh (Nuclear Science and Technology, 2016)
UV light has strongly influenced on the growth of E. coli as well as caused DNA damages. Configurations of both genomic DNA and pUC 19 plasmids extracted from E. coli were significantly changed by the exposure to UV light of 254 nm and DLT, an extract of Ganoderma lucidum Lingzi mushroom. The results also revealed the radio-protective effects of DLT to UV radiation. By adding 2% DLT to its culturing suspension, the growth of E. coli was significantly decreased, whereas a low DLT amount of about 0.5% slightly improved its growth, indicated that the DLT extract can be used as a promising protective substance against UV radiation. At the molecular level, the radio-protective effects of DLT were observed for both UV treated DNA and protein. Thus, DLT can protect DNA in vivo, but not in vitro. This effect was also observed for Taq polymerase, suggested that the radio-protection effect of DLT may due to it accelerated the degradation of radicals or species that produced in the suspensions during UV exposure.